Measurement of the Intracochlear Hypothermia Distribution Utilizing Tympanic Cavity Hypothermic Rinsing Technique in a Cochlea Hypothermia Model - Bader, Werner; Gottfried, Timo; Degenhart, Gerald; Johnson Chacko, Lejo; Sieber, Daniel; Riechelmann, Herbert; Fischer, Natalie; Hoermann, Romed; Glueckert, Rudolf; Schrott-Fischer, Anneliese; Schmutzhard, Joachim (Frontiers in Neurology, 2021)
Introduction: Cochlea implants can cause severe trauma leading to intra-cochlear apoptosis, fibrosis and eventually to loss of residual hearing. Mild hypothermia has been shown to reduce toxic or mechanical noxious effects, which can result in inflammation and subsequent hearing loss. This paper evaluates the usability of standard surgical otologic rinsing as cooling medium during cochlea implantation as a potential hearing preservation technique. Material and Methodes Three human temporal bones were prepared following standard mastoidectomy and posterior tympanotomy. Applying a retrocochlear approach leaving the mastoidectomy side intact temperature probes were placed into the basal turn (n=4), the middle turn (n=2), the helicotrema and the modiolus. Temperature probe positions were visualized, by µCT imaging and manually segmented using Amira® 7.6. Through the posterior tympanotomy the tympanic cavity was rinsed at 37° Celsius in the control group, at room temperature (in the range between 22 and 24° Celsius) and at iced water conditions. Temperature changes were measured in the preheated temporal bone. In each temperature model rinsing was done for 20 minutes at the prespecified temperatures measured in 0.5 second intervals. At least 5 repetitions were performed. Data was statistically analyzed using pairwise t-tests with Bonferroni correction. Results: Steady state conditions achieved in all three different temperature ranges were compared in periods between 150 and 300 seconds. Temperature in the inner ear started dropping within the initial 150 seconds. Temperature probes placed at basal turn, the helicotrema and middle turn detected statistically significant fall in temperature levels following body temperature rinses. Irrigation at iced conditions lead to the most significant temperature drops. The curves during all measurements remained stable with 37° C rinses. Conclusion: Therapeutic hypothermia is achieved with standard surgical irrigation fluid and temperature gradients are seen along the cochlea. Rinsing of 120 seconds duration results in a therapeutic local hypothermia throughout the cochlea. This otoprotective procedure can be easily realized in clinical practice.